Effect of Integrated Yoga Protocol on Dysmenorrhea among women aged 16-40 years- An open labeled comparative clinical study - Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2021)
Background: Yogic practices help decreasing the pain and disability caused by dysmenorrhea in menstruating women. Aim and Objective: This study aimed to assess the effects of 8 weeks of Asana (postures) with Pranayama (control of Breath) and no yogic practices on menstrual pain and disability scores in menstruating women of 16-40 years of age. Subjects and Methods: A total of 60 participants (mean age: 24.35 years) were divided into a yoga (Y) group and control (C) group. Participants attended a 45-min session every day for 8 weeks (2 menstrual cycles) before meals in a community hall. Pain scores, WaLIDD scores, level of functioning, severity of the associated symptoms assessed before and after the interventions in both the groups. Statistical Analysis: Changes in scores were analyzed with the Wilcoxon signed rank test for each group. Pre-post results were compared for all the measured values. P < 0.05 was considered statistically significant. Results: Based on the % difference from the baseline scores, Intervention group (Y) showed significant improvements in pain scores on VAS scale (81.5%), WaLIDD score (71.45%), sites of pain (73.3%) and total duration of pain (66.69%) and overall improvement in the other systemic symptoms associated with dysmenorrhea. Conclusions: The 8-week yoga intervention for menstruating women improves the functioning of women suffering from dysmenorrhea by decreasing the intensity, duration, sites and symptoms associated with dysmenorrhea.